ENVIRONMENTAL DISPOSAL OF LARGE-TONNAGE INDUSTRIAL WASTE FOR THE PRODUCTION OF FIRE EXTINGUISHING POWDERS - B. Sapargaliyeva; A. Naukenova; Sh. Shapalov; B. Alipova; J. R. Illari (Academic Journal of Physical and Chemical Sciences, 2019)
The given research presents the classification of fire extinguishing and explosion suppression compositions. Phosphogypsum is a large-scale waste from the production of orthophosphoric acid, obtained by extraction from phosphorite with sulfuric acid. The presence in phosphogypsum of pollutants in the form of phosphorus and fluorine compounds, during the preparation of which sludge wastes are emitted into the air, adversely affecting not only the human body, but also the environment. As a result of studies conducted on the study of multi-purpose industrial wastes, including phosphogypsum and its use as flame retardants, the study of reactive, physicochemical, thermal and fire-resistant properties, it is shown for the first time that it is useful as a localization and extinguishing of combustible solid combustible materials and the use of phosphogypsum in fire extinguishing powder formulations.